Recent advances in biofabricated gut models to understand the gut-brain axis in neurological diseases - Han, Hohyeon; Jang, Jinah (Frontiers in Medical Technology, 2022)
Increasing evidence has accumulated that gut microbiome dysbiosis could be linked to neurological diseases, including both neurodegenerative and psychiatric diseases. With the high prevalence of neurological diseases, there is an urgent need to elucidate the underlying mechanisms between the microbiome, gut, and brain. However, the standardized animal models for these studies have critical disadvantages for their translation into clinical application, such as limited physiological relevance due to interspecies differences and difficulty interpreting causality from complex systemic interactions. Therefore, alternative in vitro gut–brain axis models are highly required to understand their related pathophysiology and set novel therapeutic strategies. In this review, we outline state-of-the-art biofabrication technologies for modeling in vitro human intestines. Existing 3D gut models are categorized according to their topographical and anatomical similarities to the native gut. In addition, we deliberate future research directions to develop more functional in vitro intestinal models to study the gut–brain axis in neurological diseases rather than simply recreating the morphology.